Estrutura e função da proteína YacG de Klebsiella pneumoniae e seus derivados peptídicos - Garcia, Anderson [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
YacG belongs to zinc-finger's protein family discovered in E. coli. Its biological function is connected to the catalytic inhibition of DNA gyrase and stress metabolism in prokaryotes. This protein inhibits DNA gyrase (gyrase) through a bipartite mechanism where the zinc-finger domain prevents the DNA ligation to the B subunit (GyrB) and the C-terminal bindings to the A subunit (GyrA). Although it is classified as a gyrase inhibitor neither the inhibition activity of YacG from E. coli and other microorganisms against other DNA topoisomerases nor the biological activity of fragments in cellular assays has been evaluated until present. In this study, YacG from Klebsiella pneumoniae was obtained by heterologous expression and derivative peptides from this protein were synthesized by the solid-phase method. The synthetic peptides were designed to keep the native region of zinc-finger (YacGAG1), to substitute cysteines to serines (YacGAG4), to alanine (YacGAG5), to histidine (YacGAG6 and YacGAG8) and also having only the C-terminal region (YacGAG7). The inhibition assays of gyrase by the peptides and the native protein revealed that YacG, YacGAG4, YacGAG4 e YacGAG7 inhibited this enzyme and the human topoisomerase IIα (htopoIIα). However, the same was not observed for the native fragment YacGAG1, which inhibited only the htopoIIα. The results are in agreement with literature showing that solely the C-terminal region is able to inhibit the gyrase. The assays of fluorescence anisotropy indicated that these synthetic peptides interact with GyrA. Besides inhibiting the gyrase and the htopoIIα, these peptides also revealed bacteriostatic activity against gram-negative and gram-positive bacteria. A computational study by applying a molecular dynamics protocol highlighted the importance of residues I47, R46 and W40 from YacG in the process of molecular recognition and interaction with GyrB. The results...

YacG é uma pequena proteína membro da família dos zinc-fingers, descoberta em E. coli. Sua função biológica está ligada a inibição da atividade de DNA girase e ao metabolismo do stress em procariotos. YacG atua na inibição da atividade de DNA girase por um mecanismo bipartido, a região do domínio zinc-finger atua impedindo a ligação do DNA à subunidade B e a região c-terminal liga-se a subunidade A. Embora a literatura cite YacG como sendo um inibidor de DNA girase, nada foi observado a respeito da atividade de inibição de YacG de E.coli e de outras linhagens de micro-organismos frente a outras DNA topoisomerases e não foi realizado nenhum trabalho envolvendo fragmentos peptídicos desta proteína, e tampouco ensaios de inibição do crescimento celular por estes. Sendo assim YacG de Klebsiella pneumoniae foi obtida por expressão heteróloga e uma série de peptídeos derivados desta foram sintetizados pelo método de fase sólida. Os peptídeo sintéticos foram projetados de forma a manter a região zinc-finger nativa (YacGAG1), substituídos os resíduos de cisteína por serina (YacGAG4), alanina (YacGAG5), histidina (YacGAG6 e YacGAG8) e também sintetizada a sua região c-terminal (YacGAG7). Os ensaios de inibição da atividade de DNA girase pelos peptídeos sintéticos e proteína, mostraram que YacG, YacGAG4, YacGAG5 e YacGAG7 conseguem inibir a atividade desta enzima, ao contrario do fragmento nativo YacGAG1. Por outro lado YacGAG1 conseguiu inibir a atividade de Topoisomerase IIα humana juntamente com os demais peptídeos YacGAG4, YacGAG5 e YacGAG7 e proteína YacG. Os ensaios aqui apresentados corroboram com os dados apresentados na literatura onde a região c-terminal por si só é capaz de inibir a atividade de DNA girase. Os ensaios de anisotropia de fluorescência demonstraram que a interação dos peptídicos sintéticos com DNA girase se dá pela interação destes com...
Keywords: Inibidores enzimaticos; Metaloproteinas; Peptídeos - Síntese; Proteínas recombinantes; Agentes antibacterianos; Enzyme inhibitors